Glistening in glaucomatous eyes: visual performances and risk factors. (7th October 2013) - Schweitzer, Cedric; Orignac, Isabelle; Praud, Delphine; Chatoux, Olivier; Colin, Joseph
Abstract Purpose To analyse risk factors and visual performances of glaucomatous eyes with glistening in the intra‐ocular lens (IOL). Methods Prospective study performed between November 2010 and April 2011 and involving 67 consecutive glaucomatous eyes (47 patients), who previously had a phacoemulsification with a hydrophobic acrylic IOL implanted in the capsular bag. Glistening was classified in three groups of severity grade: G0 (<50 microvacuoles per mm2), G1 (50–150 microvacuoles per mm2), and G2 (>150 microvacuoles per mm2). All eyes underwent a best‐corrected visual acuity evaluation (BCVA, LogMAR scale), a complete clinical examination, a visual field test, a contrast sensitivity evaluation and a wavefront analysis of high‐order aberrations (HOAs) using a Shack–Hartmann aberrometer. Eyes with a posterior capsular opacification and a BCVA>0.30 LogMAR were excluded. Results Twenty six eyes (38.8%) had a grade 0, 12 eyes (17.9%) a grade 1 and 29 eyes (43.3%) a grade 2 of glistening severity grade. The mean follow‐up after cataract surgery was 35.2 ± 24.2 months and was significantly higher for G1 and G2 groups (p < 0.001). A higher number of topical glaucoma medication were associated with a higher glistening severity grade (p < 0.05). G1 and G2 groups had significantly lower mean contrast sensitivity values at high spatial frequencies and significantly higher loss variance (LV) values of the visual field test (p < 0.05). There was no significant difference in mean BCVA between groups (p = 0.455). Conclusions In glaucomatous eyes, glistening increased with time was associated with the number of topical glaucoma medications daily instilled and altered visual performances. It should be a consideration for glaucoma patients who are more likely to develop glistening within the IOL optic.